Open Educational Practice and Workforce Competence in Cultural Studies. Issue 1 (13th December 2021) - Funk, Johanna
This paper presents findings from the first half of a study focusing on workforce competence (WFC) and open educational practices (OEP) in a core unit for university students. Approximately 500 students per semester from across college disciplines take the unit in cultural studies. This unit has been redeveloped by our team at a university in remote northern Australia with a well-established blended delivery practice. I used developmental evaluation and content analysis to identify criteria for developing WFC skills in unit content, students' feedback, and work samples. Initial findings suggest that OEP, interdisciplinary use of educational technology and critical pedagogies embed WFC skills for many students. Students endorsed how we used technologies, OEP and unit content as vehicles for desirable skills. OEP can cultivate workforce skills in different qualifications and could sidestep the conflicting dilemmas graduates face with futures that demand flexibility and specific job fit. This short piece shares initial analysis of emergent links between OEP and WFC and points to ways OEP, related interactions and workforce skills can improve learning design strategies across the education sector.